2017
DOI: 10.3389/fphar.2017.00875
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methanolic Extract of Dandelion Roots on Cancer Cell Lines and AMP-Activated Protein Kinase Pathway

Abstract: Ethnomedicinal knowledge of plant-derived bioactives could help us in discovering new therapeutic compounds of great potential. Certainly, dandelion has been used in traditional ethno-medicinal systems (i.e., Chinese, Arabian, Indian, and Native American) to treat different types of cancer. Though, dandelion is highly vigorous, but the potential mode of action is still unclear. In the current study, the antiproliferative activity of methanolic extracts of dandelion root (MEDr) on cell viability of HepG2, MCF7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…These include sesquiterpene lactones, terpenoids, polysaccharides, and phenolic compounds (Gonzalez-Castejon, Visioli, & Rodriguez-Casado, 2012;Schutz et al, 2006;Williams, Goldstone, & Greenham, 1996). Recently, dandelion has garnered attention for its antioxidant and its anti-inflammatory effects and its possible beneficial effects against the development of obesity, cancer, and numerous cardiovascular risk factors (Jeon, Kim, & Kim, 2017;Ovadje, Ammar, Guerrero, Arnason, & Pandey, 2016;Rehman et al, 2017). Dandelion continues to be commercialized as herbal formulation mainly for its potential to prevent or ameliorate the outcome of several chronic liver disorder such liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…These include sesquiterpene lactones, terpenoids, polysaccharides, and phenolic compounds (Gonzalez-Castejon, Visioli, & Rodriguez-Casado, 2012;Schutz et al, 2006;Williams, Goldstone, & Greenham, 1996). Recently, dandelion has garnered attention for its antioxidant and its anti-inflammatory effects and its possible beneficial effects against the development of obesity, cancer, and numerous cardiovascular risk factors (Jeon, Kim, & Kim, 2017;Ovadje, Ammar, Guerrero, Arnason, & Pandey, 2016;Rehman et al, 2017). Dandelion continues to be commercialized as herbal formulation mainly for its potential to prevent or ameliorate the outcome of several chronic liver disorder such liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has many pharmacological effects. Modern pharmacological studies show that the properties of dandelion include antibacterial [ 9 , 10 ], antiviral [ 11 ], anticancer [ 12 16 ], antioxidant [ 17 ], anti-inflammatory [ 18 20 ], and antiallergic functions. In terms of the alleviation of airway inflammation, a distinctive feature of asthma, it has been reported that the organic acid components of TMHM can improve lipopolysaccharide-induced histopathological damage to tracheal tissues [ 21 ] and reduce lipopolysaccharide-induced inflammation in normal human bronchial epithelial cells [ 22 ], which could be beneficial for the treatment of acute tracheobronchitis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has many pharmacological effects. Modern pharmacological studies show that the properties of dandelion include antibacterial 6,7 , antiviral 8 , anticancer [9][10][11][12][13] , antioxidant 14 , anti-in ammatory [15][16][17] , and antiallergic functions. In terms of the alleviation of airway in ammation, a distinctive feature of asthma, it has been reported that the organic acid components of TMHM can improve lipopolysaccharide-induced histopathological damage to tracheal tissues 18 and reduce lipopolysaccharide-induced in ammation in normal human bronchial epithelial cells 19 , which could be bene cial for the treatment of acute tracheobronchitis.…”
Section: Introductionmentioning
confidence: 99%